Model of clustering of earthquakes - Barenblatt, G. I. (1981)
A two-dimensional model of the expansion of a crack in an elastic medium is considered in which friction depends on the slip rate and the modulus of cohesion depends on the speed of expansion of the crack. Elastic waves are neglected (quasi-static model). Under some conditions, the expansion of the crack is realized by the alternation of slow and fast episodes (“shocks”) of slip. This offers a possible qualitative explanation of several forms of earthquake clustering, including clustering that is premonitory to strong earthquakes.